Improving forensic healthcare: ARMED, a new telemedical examination - Taalab, Yasmeen M.; Kaufmann, Dorothea; Landmann, Aysche; Ungermann, Emily Marie; Heinze, Sarah; Stöttner, Barbara; Tsaklakidis, Anastasia; Schroff, Andreas; Konrad, Florian; Mezger, Alexander; Schlenzig, Sophia; Yen, Robert; et al. (International journal of legal medicine, 2025)
the Istanbul Convention demands care to victims of violence while upholding forensic standards. Victims, however, often seek medical help at hospitals where the availability of forensic experts is limited. This results in overlooked injuries and lost or damaged evidence, ultimately impacting court proceedings and identification of individuals at risk. The aim of this paper was to establish real-time remote guidance for distant physicians during the forensic examination of violence victims.